Macrofaunal key crustaceans in Atlantic and Mediterranean exposed sandy beaches : does knowledge on key species bio-ecology have a role in assessing global changes? - Gonçalves, Sílvia Correia (2007)
Tese de doutoramento em Biologia (Ecologia) apresentada à Fac. de Ciências e Tecnologia da Univ. de Coimbra